OPTIMALISASI PENGGUNAAN MESIN POMPA AIR PADA SARINGAN MANUAL UNTUK MENINGKATKAN KETERSEDIAN AIR BERSIH PASCA BANJIR DI DESA TUALANG BARO KECAMATAN MANYAK PAYED KABUPATEN ACEH TAMIANG - Nurmalawati; Ryan Pramanda; Dewiyana (Jurnal Masyarakat Berdikari dan Berkarya (Mardika), 2026)
Optimizing the use of water pumps in manual filters is an appropriate and applicable solution to increase clean water availability after flooding. This program not only addresses the community's immediate needs but also strengthens their self-reliance in sustainably responding to disasters.